PEMBENTUKAN KARAKTER SISWA MELALUI KEGIATAN POSITIVE CHARACTER CAMP (PCC) - Abbas, Ramadhani Andarus; Mansur, M; Budiono, Budiono (Jurnal Civic Hukum, 2017)
The imbalance of early goal of the education has made students increased their negative behaviors that lead to moral degradation in the world of education. The circumstances that encourage SMAN 4 Malang to instill good character education through formal and nonformal education. One of the non-formal education programs are through school activities, namely Character Camp (PCC). The purpose of this study to determine: (1) the background and objectives of the program Character Camp (PCC) at SMAN 4 Malang; (2) the backgroundand objectives of the program Character Camp (PCC) at SMAN 4 Malang; (3) e?ort to plant character values and the values of any character instilled in students through a program called Character Camp (PCC) at SMAN 4 Malang; (4) the e?ectiveness of the program Character Camp (PCC) in instilling character values in SMAN 4 Malang.This research was conducted at SMAN 4 Malang. The method in this study was using a qualitative approach with descriptiveresearch and ex-post facto research. Where it can facilitate researchers in collecting data and searching for information that is descriptive with interviews about events that have occurred and collection of the existing documentation. The collection of data obtained are through interview techniques and the technique of documentation. Data validity technique is by using credibility, transferability, dependability and confrmability.The results show that thebackground and objectives of the program called Character Camp (PCC) is the concern by the school SMAN 4 Malang see the development of more advanced age, but many have a negative impact for students. so as to develop a positive character for the students of SMAN 4 Malang undertaking the training of character formation program that is realized in the form Character Camp (PCC). Many positive activities of the student during the execution of Character Camp (PCC) such as: outbound, mental strengthening, hypnotherapy and socialassistance (BAKSOS). Implementation of this program is made to be interesting, fun but still contains the values of the characters in it. The values of the characters in such activities as: environmental care, social care, religious, hardworking, independent, discipline and communicative. E?ectiveness of the program Character Camp (PCC) in instilling character values to students only 80%, but it goes through the school rules and regulations the charactervalues will be maintained and even developed.